2009
DOI: 10.1002/esp.1833
|View full text |Cite
|
Sign up to set email alerts
|

Natural experiments in landscape evolution

Abstract: A natural experiment in landscape evolution is a case study of landform development in which only one element varies significantly, and for which the driving forces, initial conditions, and/or boundary conditions are well constrained. Natural experiments provide a means of testing landscape evolution theory on the large space and time scales to which that theory applies. Natural experiments can involve either steady or transient conditions. Cases with steady conditions allow one to test predictions about the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(103 citation statements)
references
References 92 publications
1
99
0
Order By: Relevance
“…This has prompted the use of paired ancient and modern stream profi les as test cases (Stock and Montgomery, 1999;Tomkin et al, 2003;van der Beek and Bishop, 2003), as well as studies of transient incision Whittaker et al, 2007a) and spatially variable erosion and rock uplift (Snyder et al, , 2003aKirby and Whipple, 2001;Lavé and Avouac, 2001;Duval et al, 2004;Whittaker et al, 2007aWhittaker et al, ,b, 2008Attal et al, 2008). Some examples of studies that use natural experiments to test landscape models are reviewed by Tucker (2009). More such studies are needed to provide a basis for evaluating and refi ning the current generation of water erosion models.…”
Section: Erosion and Transport By Overland And Channelized Fl Owsmentioning
confidence: 97%
See 2 more Smart Citations
“…This has prompted the use of paired ancient and modern stream profi les as test cases (Stock and Montgomery, 1999;Tomkin et al, 2003;van der Beek and Bishop, 2003), as well as studies of transient incision Whittaker et al, 2007a) and spatially variable erosion and rock uplift (Snyder et al, , 2003aKirby and Whipple, 2001;Lavé and Avouac, 2001;Duval et al, 2004;Whittaker et al, 2007aWhittaker et al, ,b, 2008Attal et al, 2008). Some examples of studies that use natural experiments to test landscape models are reviewed by Tucker (2009). More such studies are needed to provide a basis for evaluating and refi ning the current generation of water erosion models.…”
Section: Erosion and Transport By Overland And Channelized Fl Owsmentioning
confidence: 97%
“…In addition, both armouring and clast weathering play a vital role in the erosional development of engineered landforms, motivating the development of 1D models of these processes and their interaction with erosion and transport Willgoose and Sharmeen, 2006). In addition to the problem of grain sizes, the broader issue of lithology also stands out as an important unknown: while variations in lithology clearly impact landform evolution and erosion rates, there remains a need to quantify the relationship (Cohen et al, 2008;2009).…”
Section: Knowledge Gaps In Geomorphic Processesmentioning
confidence: 98%
See 1 more Smart Citation
“…Uncertainties in initial and boundary conditions, as well as spatial and temporal heterogeneity in rock type and sediment size, introduce substantial complexity into model verification exercises. Nevertheless, studies exploiting natural experiments, or landscapes where initial conditions, boundary conditions, and/or parameter values are particularly well constrained (Tucker, 2009), have seen some success in validating models (e.g., Stock and Montgomery, 1999;Tomkin et al, 2003;van der Beek and Bishop, 2003;Valla et al, 2010;Hobley et al, 2011). The SPACE model makes predictions for steady-state channel slope and sediment thickness that could be validated by field or experimental studies.…”
Section: Potential For Model Validation Against Real Landscapesmentioning
confidence: 99%
“…It was also observed that erosion in some places had winnowed away topsoils, exposing a greater abundance of smaller artefacts, while concentrated flows in other parts of the study area decreased the number of small flakes. This serendipitous co-occurrence of an archaeological survey and a large-scale fluvial event is an example of a 'natural experiment'; an opportunity to evaluate the effects of a natural process that is otherwise difficult or impossible to control (Tucker, 2009). The effects observed at Nundooka were not uniform across Fowlers Gap landscape: for example, stream action in another study area knocked out previously recorded surfaces dating back to the mid-Holocene.…”
Section: Introductionmentioning
confidence: 99%